จากหน้าจอถึงความจริง: การรับรู้ข่าวสารจริงและข่าวปลอม ผ่านสมาร์ตโฟนของสังคมไทย - ศรีมะหันต์, ศุภวุฒิ; พรมจักร์, นันทกา; ปิดตลาด, ไพรทูลย์ (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 2 No 2 (2025): วารสาร มมร ยศสุนทรปริทรรศน์-ปีที่ 2 ฉบับที่ 2 (พฤษภาคม-สิงหาคม 2568), 2025)
In the digital era, smartphones have become the primary channel for Thai citizens to access news and information. Advances in technology and the rise of social media platforms have accelerated and expanded news dissemination, while simultaneously creating opportunities for the uncontrolled spread of fake news and disinformation. This article aims to analyze Thai society’s perception of real and fake news through smartphone usage, employing the theoretical frameworks of agenda-setting, gatekeeping, and the concept of information disorder proposed by Wardle and Derakhshan. The findings indicate that Thai news consumption behaviors rely heavily on social media sources, lack systematic fact-checking prior to sharing, and are influenced by platform algorithms that generate echo chambers and filter bubbles. These dynamics contribute to biased perceptions and increase the risk of misinformation, particularly regarding political and social issues, which may undermine public trust and long-term social stability. The article proposes several key strategies: promoting media literacy and digital literacy across all sectors, integrating these competencies into the national education system, and fostering collaboration among government agencies, private sectors, online platforms, and civil society. Such collaborative mechanisms will enhance the effectiveness of news filtering systems and strengthen society’s resilience against information disorder. Ultimately, these efforts aim to safeguard political and social security, while equipping citizens with sustainable skills to critically engage with the challenges of digital media in the twenty-first century.